The Tufan Nuh in Surah Al-Ankabut Perspective of Syeikh Tantawi Jauhari's Scientific Interpretation - Kurniawan, Desma; Maksum, Muh Nur Rochim; Hafidz (Dirasah International Journal of Islamic Studies, 2024)
The Qur'an is a book of guidance for science, modern science, law, wisdom, truth, justice, aqidah, and morality that has been applied to straighten out human actions as a way of salvation in the world hereafter. How to understand the Qur'an is by the method of tafsir, which has been written by many mufassir, one of which is tafsir ilmi. The purpose of this study is to describe the great flood at the time of Nuh from the perspective of scientific explanation of Sheikh Tantawijauhari, the primary source of his tafsir book entitled Al-Jawahir fi Tafsir Al-Qur'an Al-Karim. This research uses a library research method with a descriptive analysis approach. The data collection method used is documentation. The result of the study is Tufan Nuh in Surah Al'-Ankabut referred to as tasliyah the sadness of the Prophet Muhammad SAW, steadfastness in preaching tawhid, filling the age of human life with mujahadah, Allah saves believers and punishes those who disbelieve, the loss of several continents and the extinction of several species of animals on earth. So it will be revealed that the great flood turned out to have extraordinary wisdom for humans.